THE USAGE OF VEGETABLE RAW MATERIALS IN THE PRODUCTION OF COTTAGE CHEESE PRODUCTS - Zhakupova Gulmira Nurtaevna; Sagandyk Asem Talgatovna; Muldasheva Aknur Gayratovna; Akisheva Elmira Kudaibergenovna; Tomasikova Samal (Academic Scientific Journal of Chemistry, 2019)
. In the present work the technology of production of cottage cheese products based on the use of herbal supplements is considered. Fiber and stevia are used as products that increase the nutritional value of the product. The results of experimental studies show that the addition of plant components have a positive effect on the quality and nutritional value of the product.